Evaluasi Kurva Beban Harian Energi Listrik Terhadap Kapasitas Transformator Untuk Keperluan Pengembangan Jaringan Distribusi Fakultas Teknik Universitas Riau (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Faculty of Engineering is one of faculty which belongs to University of Riau, which consists of 10 buildings as follows: C building, 3 of chemical engineering laboratory buildings, 3 of civil engineering laboratory buildings, mechanical engineering laboratory, and electrical engineering laboratory. The electric power installed in the Faculty of Engineering supplied from PLN with 2 pieces of transformer which capacity of 2 x 400 kVA. The large of attached power and used power still need to be evaluated to forming the daily load curve considering that the engineering faculty which keep on experiencing development and construction that has been planned in the future. From the curve is formed it will be known how the electrical conditions in the Faculty of Engineering as well as for the achievement of a reliably electrical installation systems, safe, and used as efficiently as possible. From the analysis of measurements for 1 month and the calculation of the maximum load of 286,7 kVA, so that the remaining power which can be used for development and construction is 513,3 kVA.Keywords:Distribution System, Load Curve, Electric Power